The utilization potential of rice husk as an alternative energy source for power plants in Indonesia - Anshar, Muhammad (2013)
The utilization of rice husk as an alternative fuel for the power plant in Indonesia is still under study. In present, steam power plants in Indonesia are still using coal fuel. This study was conducted to obtain data on the development potential of rice husk within 12 years duration. The potential of rice husk for each province was obtained by analyzing the rice production of 22 provinces that have rice production greater than 1 million tons per year. The study shows that the potential of rice husk and potential electrical energy increased by about 36.8% within 12 years or an average increase of around 3.1% per year. For the potential of rice husk in 22 provinces, the total gain was estimated 12.76 × 106 tons which is equivalent to 6.62 × 106 tons of coal or equivalent to 3.68 × 106 tons of oil. The available capacity of power plants is around 5,664 MW with the potential of electric energy is around 49,622 GWh. This potential is equivalent to 50% of the energy needs of coal in Indonesia in 2011, which was about 99,312 GWh. In conclusion, rice husk is indeed potential to be used as an alternative fuel in power plants thanks to its increasing yearly production and ability for distribution to all provinces in Indonesia.